Developing an English web-based learning application for senior high school students - Haiyudi Haiyudi; Suprayuandi Pratama (International Journal on Education Insight, 2026)
This research focuses on the development of LearningMu, a web-based English learning application designed for senior high school students in rural areas, particularly Belitung Regency, Indonesia. The initiative was motivated by persistent obstacles such as limited digital facilities, low student engagement in conventional classrooms, and the lack of cultural contextual learning resources. A research and development method was applied with the ADDIE development approach, enabling iterative refinement of the system based on continuous feedback from both teachers and students. The primary goal was to create an interactive, user-friendly, and accessible platform that supports autonomous learning. Trial implementation involving 30 students and three English teachers demonstrated that LearningMu provides an attractive interface, straightforward navigation, and locally relevant materials. The integration of multimedia resources, gamified quizzes, and monitoring features is hoped to enhance students’ motivation, language comprehension, and collaboration between schools and parents. Overall, the findings suggest that LearningMu is an effective and innovative tool to reduce educational disparities in underserved communities, and its modular design offers potential for wider adoption in similar contexts.